Model Kegiatan Microteaching untuk Mengembangkan Keterampilan Melaksanakan Pembelajaran Matematika Berpusat pada Siswa - Susilahudin Putrawangsa; Muhammad Syawahid (Universitas Hamzanwadi, 2018)
The current research intends to identify the characteristics of microteaching model that is valid, effective and practical to develop prospective mathematics teachers’ competencies in conducting student-centered instructions. It is a development research carried out according to Educational Design Research. The findings suggests that the characteristics of microteaching model to develop prospective mathematics teachers’ competencies in conducting student-centered instructions are: (1) a microteaching which is carried out in a cycle process consisting of planning, implementing, observing, and evaluating student-centered teaching and learning where each participant acts as a teacher and evaluators in turn. (2) a microteaching that is conducted in form of Peer Microteaching by Self-Study Group where they peer supervise each other (Peer Supervision). (3) a microteaching that has a teacher observation and evaluation protocol that is conducted by themselves (Self-evaluation) and others (Peer Evaluation) and focuses on particular aspects of teacher performance in implementing student-centered instructions those are claimed to important and possible to be refined at the moment (At-the-time improvement). (4) a microteaching which is carried out in a progressive complexity of teaching environment, that is starting from teaching a less complex to a more complex classroom setting.